Challenges in Harmonized Assessment of Heavy Metals in the Adriatic and Ionian Seas - Berto, Daniela; Formalewicz, Malgorzata; Giorgi, Giordano; Rampazzo, Federico; Gion, Claudia; Trabucco, Benedetta; Giani, Michele; Lipizer, Marina; Matijevic, Slavica; Kaberi, Helen; Zeri, Christina; Bajt, Oliver; et al. (Frontiers in Marine Science, 2020)
The Adriatic-Ionian region (ADRION Region) shows strong development in terms of urban expansion in coastal and inland areas as well as increasing maritime traffic and offshore hydrocarbon extraction activities. A serious risk of pollution arises from hazardous substances requiring reliable and coherent monitoring and assessment programs. EU Directives (WFD – Water Framework Directive, MSFD – Marine Strategy Framework Directive) and Barcelona Convention protocols, aim to assess the level of pollution with the objective to implement measures to prevent and/or mitigate impacts on the marine environment. This high level integration process has to be based on common and agreed protocols for monitoring of contaminants. Aiming to share best practices to encourage a harmonized implementation of monitoring and assessment of contaminants, an extensive review of monitoring and analytical protocols adopted by six EU and non-EU countries along the Adriatic and Ionian seas was carried out in the framework of the Interreg Adrion project HarmoNIA (Interreg V-B Adriatic-Ionian (ADRION), 2018–2020). This paper presents a methodological proposal to define a common protocol for the evaluation of the metal contamination of seawater, sediment and biota. Contaminants have been chosen following preliminary consultations among countries of the ADRION area, considering objectives of WFD and MSFD, as well as Environmental Impact Assessment (EIA) procedures for offshore platforms. Information was gathered relative to matrix characteristics and quality assurance/quality control of the analytical performance (sample preservation, analytical methodology, reference materials, limit of detection, and limit of quantification, accuracy, reproducibility, etc.). The comparison of information provided by laboratories of nine institutions highlighted the request for harmonization in terms of sampling procedures, matrix characterization, preservation procedures, analytical methods and LOQ values. Although appropriate environmental quality standards for biota and sediment matrices should be established at national level and also through regional and sub-regional cooperation, as required by the WFD and MSFD, the proposed LOQ values, even if challenging, represent a benchmark and a stimulus to optimize analytical performance, to ensure the best level of protection to the coastal and offshore environment in the ADRION Region.